The Integration of Tawakal Values in Islamic Religious Education Learning: A Conceptual Analysis of the Al-Hikam Perspective by Ibn Athaillah al-Sakandari - Fudailah Alfain; Sinta Nuriyah; Mohammad Wakhyudi; Zamach Syari; Ahmad Syifauddin; Moch. Mahdiyan Nasikhin; Meylinda Khusnan Aprilia; Siti Khafiyatul Ulwiyah; M. Husni Mubarak (Edumaspul: Jurnal Pendidikan, 2026)
This research aims to reconstruct the concept of tawakal in the perspective of the book Al-Hikam by Ibn Athaillah al-Sakandari and formulate its integration in the learning of Islamic Religious Education (PAI). In the modern era, the distortion of understanding of tawakal often gives birth to a fatalistic (passive) attitude or conversely, rationality without a spiritual dimension that triggers anxiety. Using qualitative methods through library research and philosophical-pedagogical approaches, this study analyzes the content of the book of Al-Hikam as a primary source. The findings of the study show that in Ibn Athaillah's view, tawakal is not a passive attitude, but a balance between submission of the heart (the inner aspect) and obedience in endeavor (the birth aspect). Pedagogically, tawakal values can be integrated into PAI learning through the internalization of character values, teacher examples, and reflective processes. This integration functions as an instrument of emotional regulation for students, which is parallel to the concepts of self-efficacy and perceived control in psychology, so as to be able to form a student mentality that is resilient, optimistic, and has inner peace in facing academic and social challenges. Abstrak Penelitian ini bertujuan untuk merekonstruksi konsep tawakal dalam perspektif kitab Al-Hikam karya Ibnu Athaillah al-Sakandari serta merumuskan integrasinya dalam pembelajaran Pendidikan Agama Islam (PAI). Di era modern, distorsi pemahaman terhadap tawakal sering kali melahirkan sikap fatalistik (pasif) atau sebaliknya, rasionalitas tanpa dimensi spiritual yang memicu kecemasan. Dengan menggunakan metode kualitatif melalui studi kepustakaan (library research) dan pendekatan filosofis-pedagogis, penelitian ini menganalisis konten kitab Al-Hikam sebagai sumber primer. Temuan penelitian menunjukkan bahwa dalam pandangan Ibnu Athaillah, tawakal bukanlah sikap pasif, melainkan keseimbangan antara ketundukan hati (aspek batin) dan ketaatan dalam berikhtiar (aspek lahir). Secara pedagogis, nilai tawakal dapat diintegrasikan dalam pembelajaran PAI melalui internalisasi nilai karakter, keteladanan guru, dan proses reflektif. Integrasi ini berfungsi sebagai instrumen regulasi emosi bagi peserta didik, yang paralel dengan konsep self-efficacy dan perceived control dalam psikologi, sehingga mampu membentuk mentalitas siswa yang tangguh, optimis, dan memiliki ketenangan batin dalam menghadapi tantangan akademik maupun sosial.